Distinguishing naive‐ from memory‐derived human B cells during acute responses. Issue 11 (13th November 2019) - Auladell, Maria; Nguyen, Thi Ho; Garcillán, Beatriz; Mackay, Fabienne; Kedzierska, Katherine; Fox, Annette
Abstract: Objectives: A fundamental question in influenza research is whether antibody titre decline upon successive exposure to variant strains is consequent to recall of cross‐reactive memory B cells that competitively inhibit naive B‐cell responses. In connection, it is not clear whether naive and memory B cells remain phenotypically distinct acutely after activation such that they may be distinguished ex vivo . Methods: Here, we first compared the capacity of anti‐Ig and Toll‐like‐receptor (TLR) 7/8 and TLR9 agonists (R848 and CpG) to augment human B‐cell differentiation induced by IL‐21 and sCD40L. The conditions that induced optimal differentiation were then used to compare the post‐activation phenotype of sort‐purified naive and memory B‐cell subsets by FACS and antibody‐secreting cell (ASC) ELISPOT. Results: Sort‐purified naive and memory B cells underwent robust plasmablast and ASC formation when stimulated with R848, but not CpG, and co‐cultured with monocytes. This coincided with increased IL‐1β and IL‐6 production when B cells were co‐cultured with monocytes and stimulated with R848, but not CpG. Naive B cells underwent equivalent ASC generation, but exhibited less class‐switch and modulation of CD27, CD38 and CD20 expression than memory B cells after stimulation with R848 and monocytes for 6 days. Conclusion: Stimulation with R848, IL‐21 and sCD40L in the presence of monocytes induces robust differentiation and ASC generation from both naive and memory B‐cells. However, naive and memory B cells retain key phenotypic differences after activation that may facilitate ex vivo discrimination and better characterisation of acute responses to variant antigens. Abstract : This study contrasts the requirements and outcomes of human B‐cell subset differentiation in vitro . R848 induced more potent B‐cell differentiation than CpG when combined with sCD40L and IL‐21, an effect that was mediated via monocyte activation by R848 but not by CpG. Naive and memory B cells retained key phenotypic differences after activation that may facilitate ex vivo discrimination and better characterisation of acute responses to variant antigens.